PENGGUNAAN INDIRECT EVIDENCE (ALAT BUKTI TIDAK LANGSUNG) DALAM PROSES PEMBUKTIAN DUGAAN PRAKTIK KARTEL DI INDONESIA OLEH KPPU - Ibnu Akhyat (Faculty of Law - Tarumanagara University, 2019)
The regulation concerning business competition law in Indonesia is regulated in Law Number 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition which was enacted on March 5, 1999 and entered into force one year later. With the enactment of Law No. 5 of 1999 every business actor must implement provisions on how to run his business activities in a fair and conducive manner. In the case of alleged violation of Law Number 5 Year 1999, both Article 5, Article 9, and Article 11, require fulfillment of agreement element to prove that violation of the provisions of those Articles has occurred. However, since the cartel is usually established and done in secret, the proof of the existence of the cartel agreement creates a problem. The Monopoly Practices Law and Unfair Business Competition in Indonesia have not regulated the use of indirect evidence as evidence to prove the occurrence of a cartel. In such case, KPPU is difficult to find any written agreement or other document that explicitly contains agreement on price, marketing area, or production of goods and / or services among business actors.